Influential Factors On The Political Orientation Of Young Female Voters - Hasna, Safira; Arindita, Ruvira; Dinda, Tarisha (JURNAL TRIAS POLITIKA, 2025)
Political orientation shapes an individual's voting behavior and influences their participation in elections. Since the 2019 general elections (Pemilu), there has been a significant increase in female and young voters. Various factors including information about candidates, social image, credibility, and women’s empowerment contribute to their political decisions. Women’s empowerment, particularly in addressing issues like harassment, violence, and discrimination, plays a crucial role in enhancing self-strength, independence, and decision-making abilities, enabling greater political participation. Therefore, the objective of this research is to analyze the factors influencing the political orientation of young female voters specifically it eamines how information access, social influence, and women’s empowerment shape their political preferences and decision-making processes. Using a survey method, data were collected from 200 respondents aged 17-39 years and analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach. This method helps determine the extent to which information access, social influence, and empowerment impact on political orientation. The findings reveal that these factors significantly shape young female voters’ political preferences. Information and awareness contribute to their knowledge of candidates and policies, social influence affects their perception of credibility, and empowerment fosters independent political engagement.